Maximal oxygen uptake, total metabolic energy expenditure, and energy cost in swimmers with physical disabilities - Feitosa, W.G. (2019)
The purpose of this study was to assess the maximum oxygen uptake (V̇ O2max), the total metabolic energy expenditure (_Etot), and the energy cost (C) measured as the speed of V̇ O2max in swimmers with physical impairments. Eleven swimmers performed an Nx200- m front crawl test from a low to all-out speed and data were obtained at maximum aerobic power. The oxygen uptake was measured breath-by-breath by a telemetric gas exchange system. The _Etot was calculated from the aerobic and anaerobic pathways at maximal intensity. The C was obtained by the ratio of the _Etot and the mean swimming speed. The V̇ O2max was 38.2 ± 8.3 mL.kg. min−1, the _E tot was 191.9 ± 51.7 kJ, and the C was 0.8 ± 0.2 kJ.m−1. The energy contribution of the aerobic pathway was higher (p < 0.001) than that of both the anaerobic pathways, which were similar (p > 0.05). There was no gender effect on the results of the energy contributions (p > 0.05). The anaerobic lactic pathway contribution was higher in male than in female swimmers (p < 0.05). The V̇ O2max and C were higher in swimmers who were less affected by physical impairment. The energy contribution of the aerobic pathways was similar for males and females.